The influence of memorable tourism experiences, place attachments and place identity in enjoying local culinary food on the revisit intention the old city of Semarang - Satria Nugraha; Harmanda Berima Putra (SEAN Institute, 2024)
The study investigates influence of memorable tourist experiences, place attachment, and place identity local culinary delights while revisit intention the Old City of Semarang. The type of data used is primary data is data obtained directly from sources or respondents. The sample in this study were tourists in the Old City of Semarang 186 respondent. The sampling technique is convenience sampling. Where the target population meets the criteria. The research results show that a memorable tourist has a positive revisit intention. Place attachment has a positive effect on revisit intention. Place identity has a positive effect on the revisit intention.